The Hyperactive Foreign Policy of a Rentier State: The Case of Qatar (Politeja, 2025)
The article examines Qatar’s foreign policy during the reign of Emir Hamad bin Khalifa Al Thani (1995–2013), focusing on the foundations and instruments of its ambitious, hyperactive, and transformative approach. It highlights how this small rentier state developed and adapted its foreign policy strategy over time. Article frames the hyperactive foreign policy of a small state as a temporal phenomenon, pointing out to the unintended consequences of a hyperactive foreign policy leading eventually to its recalibration.